Simple algorithm for estimating the effects of reinforcement loadings and arrangements on composite properties - Wan Ibrahim, W. M. A; Yeoh, C. K.; Teh, P.L.; Khairel Rafezi, Ahmad; Ruhiyuddin , Mohd Zaki (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.